Recent Advances in Organic Thermoelectric Materials: Principle Mechanisms and Emerging Carbon-Based Green Energy Materials - Yinhang Zhang (Polymers, 2019)
Thermoelectric devices have recently attracted considerable interest owing to their unique ability of converting heat to electrical energy in an environmentally efficient manner. These devices are promising as alternative power generators for harvesting electrical energy compared to conventional batteries. Inorganic crystalline semiconductors have dominated the thermoelectric material fields; however, their application has been restricted by their intrinsic high toxicity, fragility, and high cost. In contrast, organic thermoelectric materials with low cost, low thermal conductivity, easy processing, and good flexibility are more suitable for fabricating thermoelectric devices. In this review, we briefly introduce the parameters affecting the thermoelectric performance and summarize the most recently developed carbon-material-based organic thermoelectric composites along with their preparation technologies, thermoelectric performance, and future applications. In addition, the p- and n-type carbon nanotube conversion and existing challenges are discussed. This review can help researchers in elucidating the recent studies on carbon-based organic thermoelectric materials, thus inspiring them to develop more efficient thermoelectric devices.